Utilization of Yard Land for Healthy Gardens Based on TOGA Waste Technology as an Effort to Support Independent Community Health Post the COVID-19 Pandemic - Febriyanti Febriyanti; Djuna Lamondo; Novri Youla Kandowangko; Wirnangsi Din Uno; Muh. Nur Akbar (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
This article is based on the Community Service Program through the Thematic Village Development Community Service program at Gorontalo State University. The aim is to accelerate the achievement of SDGs (Sustainable Development Goals) Point 3 (ensure a healthy life and encourage prosperity for all people at all ages) in Mohungo Village, Tilamuta District, Gorontalo Regency, Gorontalo Province after the COVID-19 pandemic. The solution offered from this program is the development of healthy gardens in yards using TOGA (Family Medicinal Plants) waste technology. TOGA waste is a technology for utilizing used consumables as a means for planting TOGA. Implementation of activities includes observation and surveys, outreach and education, making healthy parks, and launching programs. Based on the stages of the activities that have been carried out, it can be concluded that the implementation of making a Toga waste garden is very beneficial for the community and the government, namely by increasing public knowledge, especially PKK mothers, in utilizing plastic waste as a planting medium and planting family medicinal plants. Community involvement in assisting each stage and process from start to finish is a form of community concern for the environment.